2009
DOI: 10.1089/lrb.2008.1025
|View full text |Cite
|
Sign up to set email alerts
|

Histological Findings Compared with Magnetic Resonance and Ultrasonographic Imaging in Irreversible Postmastectomy Lymphedema: A Case Study

Abstract: Postmastectomy edema is a current complication after axillary lymph node dissection in cases of breast cancer treatment. Staging is important in order to select those patients who can benefit from complex physical therapy (CPT). Different imaging techniques can be used to evaluate the edema. Ultrasonography (US) is a harmless, cheap, and easily applicable technique to visualize the dermal and subcutaneous tissue, but interpretation of the obtained images is not always evident. The aim of this study was to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…4(b)). To our knowledge, a lot of research work regarding fibrosis in lymphedematous skin only emphasized the overproduction and deposition of collagen during lymphedema (Tassenoy et al ., 2009). Our results demonstrated that the morphology of collagen showed great changes during the development of lymphedema.…”
Section: Resultsmentioning
confidence: 99%
“…4(b)). To our knowledge, a lot of research work regarding fibrosis in lymphedematous skin only emphasized the overproduction and deposition of collagen during lymphedema (Tassenoy et al ., 2009). Our results demonstrated that the morphology of collagen showed great changes during the development of lymphedema.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the gain in volume is partly due to the growth of adipose tissue. 32 Therefore, conservative decongestive physical therapy (CPT) is not likely appropriate for this subgroup as CPT will not reduce hypertrophied adipose tissue. In patients where diffuse or honeycomb lymphedema patterns predominate on MRI, appropriate CPT can still ameliorate the volume of the edema.…”
Section: Discussionmentioning
confidence: 99%
“…In patients where diffuse or honeycomb lymphedema patterns predominate on MRI, appropriate CPT can still ameliorate the volume of the edema. 32 MR has the potential to recognize early evidence of fluid accumulation that may be overlooked by current standards of clinical assessment. Early diagnosis and nonpharmacologic interventions should be implemented as soon as possible after surgery when they are more likely to be effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Their observations provide valuable insights into the relationship between in vivo imaging attributes of lymphedema, including dermal edema and subcuticular adipose signals, and their corresponding microscopic, histological confirmation. Insights of this type will continue to refine the clinicians' ability to diagnose and stratify the severity of the cutaneous response to lymphatic vascular insufficiency.…”
mentioning
confidence: 97%